ENVIRONMENTAL INDICATORS FOR THE ASSESSMENT OF QUALITY OF LIFE - MUKMARAM ALI, KANGI, F.E; ODE H.O (International Journal of Multidisciplinary Research and Studies, 2020)
This paper deals with quality of life in terms of the environment and develops a system of indicators to assess this. An improvement in quality of life is that the main aim of sustainable development and is evaluated by applying various factors and indicators. The environmental dimension is one among the foremost influences on quality of life, and this may be assessed by applying the subsequent groups of indicators: environmental quality, environmentally responsible behavior and consumption of environmental services. These groups are related because responsible behavior incorporates a positive impact on environmental quality and ends up in greater consumption of services provided by the environment. This paper presents the concept of assessing the environmental dimension in quality-of-life measurements and therefore the main assoc1.